Kontribusi Timbulan Sampah Pangan di Kabupaten Penyangga Kota Surakarta - Saputro, Wahyu Adhi; Ulfa, Amalia Nadifta; Helbawanti, Octaviana (Suluh Pembangunan : Journal of Extension and Development, 2023)
Food waste is an issue in various regions, especially the consequences of waste. Impact of food waste will have an impact on food security, the environment and the economy. This study aims to determine the contribution of food waste produced in buffer districts in Surakarta City, namely Sukoharjo, Klaten, Wonogiri, Sragen and Boyolali regencies. The data used is secondary data originating from relevant sources such as BPS (Central Statistics Agency) and SIPSN (National Waste Management Information System). The data used is time series data from 2019 to 2021 with the contribution analysis method. Research results, it was found that in 2019, Sragen Regency had the highest food waste generation reaching 145,252 tons with a contribution value of 8.53%. In 2020 Sragen Regency is still in highest position with food waste generation of 145,683 tons with a contribution value of 7.82%. In 2021, the highest waste generation occurred in Sragen Regency with 159,822 tons of waste generation followed by Klaten Regency with 145,262 tons of food waste generation and the contribution value reached 6.49%. There needs to be awareness from the public to consume food wisely so as not to cause an increase in the volume of waste.